Couples' discussion of sexuality with their adolescent children similarities and differences - Quiray, Mylen Mirasol C.
In the area of sexuality, parents are considered as the ideal source of information for adolescents. With their experience coupled with concern for their children, parents are the best option as far as discussions of sexuality are concerned. The study examined fathers and mothers of adolescents who are couple pairs - exploring their similarities and differences, if any, in homes where both fathers and mothers discussed sexuality; father alone, and mother alone discussed sexuality; and neither father nor mother discussed sexuality. The paper provided a unique perspective on husband and wife pairs and how they differ on sexuality discussions with their adolescent children, to be able to have a better understanding of the extent to which fathers and mothers of the same adolescent children are leveled up in discussions on sexuality with their adolescent children. The study shows that only 7 percent of both fathers and mothers discussed sexuality with their adolescent children. There are more mother-only than father-only who discussed sexuality with their adolescent children, as evident in 17 percent of mothers and 11 percent of fathers.Still, majority of fathers and mothers (66%) did not have such discussions. Generally, for the four groups examined in the study, only age and socio-economic status are significantly associated with discussions on sexuality with adolescent children. Fathers and mothers who discussed sexuality are significantly older and of higher socio-economic status than those who neither discussed sexuality with their adolescent children.